Activatable NIR Fluorescence/MRI Bimodal Probes for in Vivo Imaging by Enzyme-Mediated Fluorogenic Reaction and Self-Assembly - Yan, Runqi; Hu, Yuxuan; Liu, Fei; Wei, Shixuan; Fang, Daqing; Shuhendler, Adam J; Liu, Hong; Chen, Hong-Yuan; Ye, Deju (Journal of the American Chemical Society, 2019)
Stimuli-responsive in situ self-assembly of small molecules to form nanostructures in living subjects has produced promising tools for molecular imaging and tissue engineering. However, controlling the self-assembly process to simultaneously activate multimodality imaging signals in a small-molecule probe is challenging. In this paper, we rationally integrate a fluorogenic reaction into enzyme-responsive in situ self-assembly to design small-molecule-based activatable near-infrared (NIR) fluorescence and magnetic resonance (MR) bimodal probes for molecular imaging. Using alkaline phosphatase (ALP) as a model target, we demonstrate that probe (P-CyFF-Gd) can be activated by endogenous ALP overexpressed on cell membranes, producing membrane-localized assembled nanoparticles (NPs) that can be directly visualized by cryo-SEM. Simultaneous enhancements in NIR fluorescence (>70-fold at 710 nm) and r 1 relaxivity (∼2.3-fold) enable real-time, high-sensitivity, high-spatial-resolution imaging and localization of the ALP activity in live tumor cells and mice. P-CyFF-Gd can also delineate orthotopic liver tumor foci, facilitating efficient real-time, image-guided surgical resection of tumor tissues in intraoperative mice. This strategy combines activatable NIR fluorescence via a fluorogenic reaction and activatable MRI via in situ self-assembly to promote ALP activity imaging, which could be applicable to design other activatable bimodal probes for in vivo imaging of enzyme activity and locations in real time.